Answer:
Explanation:
Simplifying
5 + 14b = 9b + -5
Reorder the terms:
5 + 14b = -5 + 9b
Solving
5 + 14b = -5 + 9b
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '-9b' to each side of the equation.
5 + 14b + -9b = -5 + 9b + -9b
Combine like terms: 14b + -9b = 5b
5 + 5b = -5 + 9b + -9b
Combine like terms: 9b + -9b = 0
5 + 5b = -5 + 0
5 + 5b = -5
Add '-5' to each side of the equation.
5 + -5 + 5b = -5 + -5
Combine like terms: 5 + -5 = 0
0 + 5b = -5 + -5
5b = -5 + -5
Combine like terms: -5 + -5 = -10
5b = -10
Divide each side by '5'.
b = -2
Simplifying
b = -2